Kunststo(f)f : Anno'02 ... Marta Hertford. - Bouchez, Hilde; Brouns, Jesse; Bucquoye, Moniek E.; Delrue, Luc; Hoet, Jan; Tazzi, Luigi ([S.l.] : Anno'02, 2002)
Barney, Matthew ; Campana, Huberto & Fernando ; Christo and Jeanne-Claude ; Crasset, Matali ; Deacon, Richard ; Droof Design, Fortuyn/O'Brien ; Hutten, Richard ; Kapoor, Anish ; Kusolwong, Surasi ; Ladstaetter, Florian ; Meyer, Anette ; Newson, Marc ; Pesce, Gaetano ; Rehberger, Tobias ; Seyffert, Stefan ; Vogt & Weizenegger ; Young, Michael.
Kunststo(f)f, Broeimuseum, Kortrijk, 27.04.2002 - 31.08.2002
Schenking Flanders DC
boek